Burden of child and adolescent obesity on health services in England. Issue 3 (1st August 2017) - Viner, Russell M; Kinra, Sanjay; Nicholls, Dasha; Cole, Tim; Kessel, Anthony; Christie, Deborah; White, Billy; Croker, Helen; Wong, Ian C K; Saxena, Sonia
Abstract : Objective: To assess the numbers of obese children and young people (CYP) eligible for assessment and management at each stage of the childhood obesity pathway in England. Design: Pathway modelling study, operationalising the UK National Institute for Health and Care Excellence guidance on childhood obesity management against national survey data. Setting: Data on CYP aged 2–18 years from the Health Survey for England 2006 to 2013. Main outcome measures: Clinical obesity (body mass index (BMI) >98th centile), extreme obesity (BMI ≥99.86th centile); family history of cardiovascular disease or type 2 diabetes; obesity comorbidities defined as primary care detectable (hypertension, orthopaedic or mobility problems, bullying or psychological distress) or secondary care detectable (dyslipidaemia, hyperinsulinaemia, high glycated haemoglobin, abnormal liver function). Results: 11.2% (1.22 million) of CYP in England were eligible for primary care assessment and for community lifestyle modification. 2.6% (n=283 500) CYP were estimated to be likely to attend primary care. 5.1% (n=556 000) were eligible for secondary care referral. Among those aged 13–18 years, 8.2% (n=309 000) were eligible for antiobesity drug therapy and 2.4% (90 500) of English CYP were eligible for bariatric surgery. CYP from the most deprived quintile were 1.5-fold to 3-fold more likely to be eligible for obesity management. Conclusions: There is a mismatch between population burden and available data on service use for obesity in CYP in England, particularly among deprived young people. There is a need for consistent evidence-based commissioning of services across the childhood obesity pathway based on population burden.